Genome wide transcriptional profiling of Herbaspirillum seropedicae SmR1 grown in the presence of naringenin - Tadra-Sfeir, Michelle Z.; Faoro, Helisson; Camilios-Neto, Doumit; Brusamarello-Santos, Liziane; Balsanelli, Eduardo; Weiss, Vinicius; Baura, Valter A.; Wassem, Roseli; Cruz, Leonardo M.; De Oliveira Pedrosa, Fábio; Souza, Emanuel M.; Monteiro, Rose A. (Frontiers in Microbiology, 2015)
Herbaspirillum seropedicae is a diazotrophic bacterium which associates endophytically with economically important gramineae. Flavonoids such as naringenin, have been shown to have an effect on the interaction between H. seropedicae and its host plants. We used a high-throughput sequencing based method (RNA-Seq) to access the influence of naringenin on the whole transcriptome profile of H. seropedicae. Three hundred and four genes were downregulated and seventy seven were upregulated by naringenin. Data analysis revealed that genes related to bacterial flagella biosynthesis, chemotaxis and biosynthesis of peptidoglycan were repressed by naringenin. Moreover, genes involved in aromatic metabolism and multidrug transport efllux were actived.